The Effect of Wind Chill in Closed House on Broiler Performance - Hariono; R. Afnan; Sumiati; R. Fadilah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Fan settings (wind speed) in the cage must be adjusted to the age and weight of the chickens. Any movement of the wind at a certain speed will have an impact on the difference between the actual temperature read on the thermometer and the effective temperature felt by the chickens. This is because there is a cold temperature effect (wind chill effect) due to air movement. On the 1st floor of the KTM cage, there was an error setting the fan on which caused the wind speed to be higher than necessary, causing a wind chill effect. This case caused the performance of the chickens in the 1st-floor cage not to reach the target. To get the ideal temperature and wind speed in the cage, the effort needed is to adjust the fan to turn on taking into account the wind chill effect. Based on the results of considering the wind chill effect in the cage, the value of feed intake, body weight gain, and body weight at the age of 7-35 days appear to be higher with a low feed conversion value and a higher production index.